Integrated LC-MS/MS and Transcriptome Sequencing Analysis Reveals the Mechanism of Color Formation During Prickly Ash Fruit Ripening - Fei, Xitong; Wei, Yuan; Qi, Yichen; Luo, Yingli; Hu, Haichao; Wei, Anzhi (Frontiers in Nutrition, 2022)
Prickly ash peel is one of the eight major condiments in China and is widely used in cooking because of its unique fragrance and numbing taste. The color of prickly ash fruit is the most intuitive quality that affects consumer choice. However, the main components and key biosynthetic genes responsible for prickly ash fruit color have not yet been determined. To better understand the biosynthetic mechanisms and accumulation of prickly ash fruit color components, we performed an integrated transcriptomic and metabolomic analysis of red and green prickly ash fruit at different growth periods. The transcriptome analysis identified 17,269 differentially expressed genes (DEGs) between fruit of red and green prickly ash: 7,236 upregulated in green fruit and 10,033 downregulated. Liquid chromatography tandem mass spectrometry (LC-MS/MS) identified 214 flavonoids of 10 types. Flavonoids and flavonols are the main flavonoids in prickly ash, and the total flavonoid content of red prickly ash is higher than that of green prickly ash. Comprehensive analysis showed that the main colored metabolites that differed between green and red prickly ash were cyanidin-3-O-galactoside and cyanidin-3-O-glucoside, and differences in the contents of these metabolites were due mainly to differences in the expression of ANS and UFGT. Our results provide insight into the mechanisms underlying color differences in red and green prickly ash and will be useful for improving the quality of prickly ash fruit.